Calcium‐binding protein 39 promotes hepatocellular carcinoma growth and metastasis by activating extracellular signal‐regulated kinase signaling pathway. Issue 5 (29th September 2017) - Jiang, Lingxi; Yan, Qian; Fang, Shuo; Liu, Ming; Li, Yan; Yuan, Yun‐Fei; Li, Yan; Zhu, Yinghui; Qi, Jiali; Yang, Xiaodong; Kwong, Dora Lai Wan; Guan, Xin‐Yuan
Abstract : Calcium‐binding protein ( CAB39 ) is a key regulator of a group of sterile 20 kinases. Here, we report that CAB39 was frequently up‐regulated in hepatocellular carcinoma (HCC), which was significantly associated with tumor metastasis ( P = 0.000), poorer disease‐free survival rate ( P = 0.027), and poor prognosis ( P = 0.000). Ectopic expression of CAB39 in immortalized human liver cell line LO2 and HCC cell lines QGY‐7703 and BEL‐7402 could increase foci formation, colony formation in soft agar, tumor formation in nude mice, and cell motility. Silencing CAB39 expression in two HCC cell lines, Huh7 and MHCC97H, with short hairpin RNA could effectively abolish its oncogenic function. Further study found that CAB39 contributed to extracellular signal‐regulated kinase (ERK) pathway activation, and mutations of the key sites of CAB39 markedly decrease the level of phosphorylated ERK. In addition, CAB39 could promote epithelial‐mesenchymal transition by up‐regulating N‐cadherin and Fibronectin and down‐regulating E‐cadherin and α‐E‐catenin. As a result, β‐catenin nuclear translocation was increased and its downstream target gene, matrix metalloproteinase‐9, was up‐regulated. Conclusion : Taken together, our findings suggested that CAB39 played very important oncogenic roles in HCC pathogenesis and progression by activating the ERK signaling pathway. Better understanding of CAB39 may lead to its clinical application as a biomarker for a prognosis predictor and a novel therapeutic target. (Hepatology 2017;66:1529–1545).